MAPA LITOESTRATIGRÁFICO DA PARTE ORIENTAL DA BACIA BAURU (PR, SP, MG), ESCALA 1:1.000.000 - FERNANDES, Luiz Alberto (Boletim Paranaense de Geociências, 2004)
A Bacia Bauru é uma bacia continental interior do Neocretáceo (Coniaciano-Maastrichtiano), desenvolvida no centro-sul da Plataforma Sul-Americana. Acumulou uma seqüência sedimentar essencialmente arenosa, que ocorre em área de cerca de 370.000 km2. Tem por substrato rochas vulcânicas, sobretudo basaltos da Formação Serra Geral (Cretáceo Inferior). A área do mapa corresponde à parte oriental da bacia, com cerca de 180.000 km2. A seqüência neocretácea é composta por dois grupos cronocorrelatos: Caiuá (formações Rio Paraná, Goio Erê e Santo Anastácio) e Bauru (formações Uberaba, Vale do Rio do Peixe, Araçatuba, São José do Rio Preto, Presidente Prudente e Marília, incluindo os Analcimitos Taiúva). LITHOSTRATIGRAPHIC MAP OF THE BAURU BASIN EASTERN PART (PR, SP, MG), SCALE 1:1.000.000 Extended Abstract The Bauru Basin is a Late Cretaceous (Coniacian-Maastrichtian) interior continental basin developed as a result of subsidence of the central-southern part of the South-American Platform. It spreads over an area of approximately 370,000 km2 and is filled by a sandy sequence with a preserved maximum thickness of 300 meters. The substratum is made up of volcanic rocks (mainly basalts) of the Serra Geral Formation (Early Cretaceous). The map area corresponds to the eastern part of the basin, with about 180,000 km2 (west of São Paulo, southwest of Minas Gerais, northwest of Paraná), located between the coordinates 18°S to 25° S and 47° W to 54° W (Figure 1). The Upper Cretaceous sequence is composed by two partially contemporaneous groups (Figure 2): Caiuá (Rio Paraná, Goio Erê and Santo Anastácio formations) and Bauru (Uberaba, Vale do Rio do Peixe, Araçatuba, São José do Rio Preto, Presidente Prudente, and Marília formations, including the Taiúva analcimites). The intensification of the tectonic activities at the north-northeastern and eastern margins, and probably also at the northwestern margin, caused significant changes in the paleogeographic scenario, promoting progradation of alluvial fans. At the same time, climatic changes increased the humidity in the marginal zones. These changes mark the beginning of the sedimentary phase during which important fluvial systems from northeast to southwest were established between the marginal zone and the inland Caiuá Desert. During the uplift of the margins, the intrusion of several alkaline magmatic bodies cause extrusive magmatism near the eastern border (Taiúva analcimites), as well as localized silicification in the southern border. All known fossil occurrences are located in the eastern part of the basin and were paleogeographically controlled. They comprise bone remains, mainly from reptiles -crocodiles, turtles, dinossaurs -, as well as amphibians, fishes, mollusks, crustaceans, and oogones of charophytic algae. The main occurrences are from fluvial flood plain deposits and ephemeral lagoons in the interior of the basin, as well as from those of braided water flows and lagoons located in zones of marginal alluvial fans. In the interior of the basin the hot desertic condition prevailed during the two phases of sedimentation.